Therapeutic effects of sunitinib, one of the anti-angiogenetic drugs, in a murine arthritis. Issue 3 (May 2014) - Furuya, Kazuhiro; Kaku, Ying; Yoshida, Ken; Joh, Kensuke; Kurosaka, Daitaro
Abstract Objectives. The purpose of this study was to confirm the inhibitory effects of sunitinib, an angiogenesis inhibitor that targets tyrosine kinases of vascular endothelial growth factor receptor (VEGFR) family and platelet-derived growth factor receptor (PDGFR) family, on arthritis in mice with type II collagen-induced arthritis (CIA). Methods. Sunitinib at a concentration of 30 or 60 mg/kg/day was intraperitoneally administered to mice with CIA. We compared the changes in arthritis score over time, pathological score, bone density, and microvascular density in synovial membrane between the vehicle and treatment groups. Results. In the sunitinib-treated groups, the arthritis score decreased in a dose-dependent manner in comparison with that in the vehicle group. Furthermore, improvement in the pathological score, inhibitory tendency of loss in the bone density, and a decrease in the synovial microvascular density were also observed in the sunitinib-treated groups. Conclusions. Sunitinib remarkably inhibited arthritis, particularly synovial angiogenesis in a murine CIA model. This compound may be useful for treating arthritis.